Digital sharia financial and business center can be realized now - Abdurohim Abdurohim (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Why not the world's Islamic finance centers in Doha, Riyadh, Ankara, Kuala Lumpur, Jakarta, currently located in London, and even Beijing? The implementation of digital sharia finance and business is based on the policies of each Islamic country; it is estimated that the future development of Islamic solid finance and business is challenging to realize. This study emphasizes new ideas for strategies and policies for the digital center of Islamic finance and business as a driver for developing the Islamic digital finance and business ecosystem. The research used the bibliometrics analysis method. From this research, it can be concluded the research that previous researchers have done is still sectoral in nature but is the basis for researchers to develop a State of Taste and Novelty to build Islamic Finance and Business for countries with the largest Muslim community. The development of Islamic Finance and Business in a centralized manner must first be arranged on a common platform that Finance and Business is a way to improve the progress and civilization of the Islamic world because, without an agreement, there will be no Center for Islamic Finance and Business in Islamic countries.